Dairy Enterprise – 600 Lactating Cows - Dhuyvetter, Kevin C.; Smith, John F.; Harner III, Joseph P.; Brouk, Micheal (My University, 1999)
This publication describes the production costs and returns for a dairy enterprise with 600 lactating cows in a freestall system.
MF2441_1999_10
Keywords: MF2441; Economics; Livestock; MF